If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-6x + -2) + 10 = 8(-3x + -1) + 14 Reorder the terms: 4(-2 + -6x) + 10 = 8(-3x + -1) + 14 (-2 * 4 + -6x * 4) + 10 = 8(-3x + -1) + 14 (-8 + -24x) + 10 = 8(-3x + -1) + 14 Reorder the terms: -8 + 10 + -24x = 8(-3x + -1) + 14 Combine like terms: -8 + 10 = 2 2 + -24x = 8(-3x + -1) + 14 Reorder the terms: 2 + -24x = 8(-1 + -3x) + 14 2 + -24x = (-1 * 8 + -3x * 8) + 14 2 + -24x = (-8 + -24x) + 14 Reorder the terms: 2 + -24x = -8 + 14 + -24x Combine like terms: -8 + 14 = 6 2 + -24x = 6 + -24x Add '24x' to each side of the equation. 2 + -24x + 24x = 6 + -24x + 24x Combine like terms: -24x + 24x = 0 2 + 0 = 6 + -24x + 24x 2 = 6 + -24x + 24x Combine like terms: -24x + 24x = 0 2 = 6 + 0 2 = 6 Solving 2 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| n/-20=0 | | -4(15y+1)+8=20(-3y+5)-102 | | -344=8(8v-3) | | (X^3-7)/(x-2) | | 18x=288 | | 1(-4x-5)+7=4(-1x-4)+18 | | x+5=8+x | | s^2=323 | | 3+3x=3x+2 | | 3/4(2?3M)=24 | | 26/y=2 | | -147=3k-3(8k+7) | | -1(x+3)-3=-6(x+8) | | 5(x/5)-3(5)=5(x/5) | | 10=-7-3x | | -6z-9(-8z-4)=2-5(-9-z) | | 5(1-2x)+8=15 | | 6(x-3)-2(x-2)=1 | | 23=33-2(4-2w) | | 12/11•5/8 | | 12/8•5/8 | | 7(3x-2)=-39 | | -9x+3=-8x | | 9x+8=-1x-13 | | 3+.20y=2x+4 | | (n+18)+2n=90 | | -23=2x+3x+2 | | x/3-3=-2 | | 6(x/6)-6(4)=6(x/6) | | -17x+18=13 | | x-7=1-9 | | -7=5-2n+6n |